2017
DOI: 10.1016/j.marpolbul.2017.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of macrobenthic assemblages and ecological health of Yellow River Delta, China, using AMBI & M-AMBI assessment method

Abstract: a b s t r a c t a r t i c l e i n f oYellow River delta (YRD) is a typical example of a valuable coastal ecosystem that is under increasing anthropogenic threat in China. To understand the current health status of this region, three surveys in 2011 for the abiotic conditions and macrobenthic assemblages were performed. The concentration of trace metals were relatively low in the sediment at all sampling stations representing a good sediment quality. A total of 159 macrobenthic species were identified during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 55 publications
(68 reference statements)
1
6
0
Order By: Relevance
“…The comparison of the ecological health status retrieved by the AMBI method through the macrobenthic assemblages (Li et al, 2017) with our results on benthic foraminifera highlights some consistency between the two methods. Specifically, the number and the abundance of macrobenthos species are significantly higher in the outermost zone of the Yellow River delta where we assessed the good ecological status.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The comparison of the ecological health status retrieved by the AMBI method through the macrobenthic assemblages (Li et al, 2017) with our results on benthic foraminifera highlights some consistency between the two methods. Specifically, the number and the abundance of macrobenthos species are significantly higher in the outermost zone of the Yellow River delta where we assessed the good ecological status.…”
Section: Discussionsupporting
confidence: 76%
“…Other studies, using marine biotic indices (e.g., Ni et al, 2019), assessed a slight disturbance of the ecological quality of macrobenthos habitats in the northern Laizhou Bay, despite the fact that the Bohai Sea is heavily affected by anthropogenic activities. Focusing on the Yellow River Delta, Li et al (2017) have shown that the number and abundance of macrobenthos species increased towards the most external zone. Trace metals, water temperature, and depth are the main environmental variables affecting the distribution pattern of macrobenthic assemblages.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The Golden Triangle of Southern Fujian Province, which includes the cities of Xiamen, Zhangzhou, and Quanzhou in China, is a coastal ecosystem where urbanization has facilitated increased productivity and economic development [ 1 ]. However, the process of urbanization has also caused severe air pollution, soil erosion, ecosystem degradation, and biodiversity loss [ 2 ]. Pollution and the degradation of ecosystems threaten the region’s economic and social development [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…To assess the benthic ecological quality of the study area, AZTI's Marine Biotic Index (AMBI) and multivariate AMBI (M-AMBI) were calculated using AMBI version 6.0 (http://ambi.azti.es). Considering that the mangrove areas in Hainan were affected by different levels of human activities, the M-AMBI reference conditions were obtained following the method based on previous studies (Borja and Tunberg, 2011;Cai et al, 2013;Li et al, 2017;Zhou et al, 2018;Yan et al, 2020): the highest values of the Shannon index H ′ and species richness (S) in the present study were both increased by 15%, and the lowest AMBI value were selected as the M-AMBI reference condition under high quality status, e.g.,AMBI=0, H ′ =4.42, S = 20; and under bad quality status, AMBI = 6, H ′ =0, S = 0.…”
Section: Discussionmentioning
confidence: 99%